Traffic offloading technology in LTE network using MEC - Jianmin ZHANG; Weiliang XIE; Fengyi YANG; Zhouyun WU (Dianxin kexue)
Considering the current demand of low-delay and local traffic in some vertical industries,a technical scheme of LTE local shunt based on MEC was proposed,and the feasibility of the scheme was analyzed.Compared with LIPA/SIPTO scheme in 3GPP,MEC-based local streaming scheme could realize the transparent deployment of MEC platform,and the terminal does not need to support multiple APN connections,so as to provide users with a“virtual LTE local area network”experience.Finally,the problems and challenges in the application of the scheme were discussed,which could provide reference for the follow-up research and development.